Peran Peran TPQ Tarbiyyatul Aulad dalam Meningkatkan Kualitas Baca Tulis Al-Qur’an dan Pembentukan Akhlak Anak - Bening Arum Amalia; Muh Bachrul Ulum (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2021)
The instilling of Islamic values ​​needs to be given by parents to children from a young age so that later the child will have good morals in the environment where he is. With this Tarbiyyatul Aulad TPQ, it really helps parents to grow their children's sense of faith in Allah as Muslims, and grow their love for the Prophet Muhammad SAW. Therefore, it is necessary for teachers who have knowledge and good manners so that they are able to motivate, provide encouragement, provide habituation and provide examples to children. Familiarizing children to read the Koran according to the correct tajwid and makhrajil letters must also be applied from an early age so that later they can istiqomah to read the Koran regularly, for example after after praying. Moreover, during this pandemic, we must carry out positive and useful activities so that faith does not decrease and as obedient Muslims, we should always be filled with worshiping Allah. Keywords: Pandemic, Morality, Islamic values, Faith